Forms of Wechselwirkung: Simmel between Money, Love and Poverty - Cocozza, Donato; Iorio, Gennaro (Simmel Studies, 2025)
This paper analyses Simmel’s concept of “Wechselwirkung”, highlighting its role in relation to money, love, and poverty. It defines money as ”Abstraktion der Wechselwirkung“ and illustrates how the concept of exchange lies at the heart of Simmel's theory of money. Love emerges as a paradigmatic social manifestation of “Wechselwirkung”'s generativity. Poverty is interpreted as a relational position. Despite their divergent outcomes (impersonal interchangeability, unrepeatable uniqueness, relational marginality), a comparison between money, love and poverty, reveals that they all embody the notion of ambivalent sociality. Ultimately, possible interpretative insights emerge regarding digital money, the welfare crisis and hypermodern manifestations of love.